Physical education and sport teachers’ organizational democracy perceptions - Nevzat Dıncer; Enes Isıkgoz; Melike Esentas (Türk Spor ve Egzersiz Dergisi)
The purpose of this research was to analyze the physical education and sport teachers’ perceptions about organizational democracy. The research group consisted of 191 physical education and sport teachers. The research data were collected by “The Organizational Democracy Scale”. In the analysis of data, descriptive statistics, Mann Whitney-U and Kruskall Wallis-H tests were used. According to the relevant findings, the physical education and sport teachers’ organizational democracy perceptions were positive in the sub-dimensions of participation-criticism, transparency, justice, equality and accountability but not high, the teachers’ organizational democracy perceptions did not significantly vary in gender, assigned school type, marital status and education background variables, in some sub-dimensions they significantly differed in assigned geographical region and seniority variables.